Development and Validation of a TLC-Densitometric Method for Quantification of Quercetin in Smallanthus sonchifolius Extract - Nurhayati, Rachma; Adhelia, Vanessa; Purwani, Asih Imulda Hari; Pramasari, Nadia; Shoviantari, Fenita (MPI (Media Pharmaceutica Indonesiana), 2026)
This study aimed to develop and validate a thin-layer chromatography (TLC)–densitometric method for the quantitative determination of quercetin in insulin leaves (Smallanthus sonchifolius). Dried insulin leaves were extracted using the maceration method with 70% ethanol as the extraction solvent. Quercetin analysis was carried out on silica gel GF254 plates as the stationary phase, using a mobile phase consisting of n-butanol, acetic acid, and water in a ratio of 4:1:5 (v/v/v). A sample volume of 4 μL was applied onto the plate and scanned at a wavelength of 284 nm using a densitometer. Method validation was performed by evaluating linearity, selectivity, accuracy, and precision parameters. The validation results showed a good linear relationship between concentration and peak area with a correlation coefficient (r) of 0.9844. The method exhibited good selectivity with a resolution value of 2.40 and peak purity of 0.99. Accuracy values ranged from 101.4% to 102.5%, while precision testing produced a relative standard deviation value of 3.0%. The average quercetin content in insulin leaves was determined to be 0.191% (w/w). These findings demonstrate that the validated TLC–densitometric method is reliable and suitable for routine quantitative analysis of quercetin in herbal raw materials for quality control purposes.